Tokoh Sastrawan Arab Pada Era Jahiliah - Salsabila, Fika Azlia; Selviana, Ika (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2024)
The jahiliah era was famous for its nomadic life. Many literary figures were born from beautiful poetry. This study analyzes the biography of Arabic writers during the ignorant period. Where it explains abaut the life of the character, his literary works and the themes thah poets often use. The purpose of this study is to provide an overview of the biograpy of Arabic literary figures during the ignorant period. The author uses descpriptive-qualitative methods whit data analysis technique, read notes and equivalent analysis techniques. From the result of research thah Arabic writers during the ignorant period such as Umru al-Qais wrote many verses with ghazal themes. Zuhair bin Abi Sulma is famous for his wisdom poems. Nabighah Az-Zibyani who used the theme of madh to praise the king. Lubaid bin Rabiah who wrote a lot of madh and ratsa’ themes. As well as Khansa, the eminent female poets who poured a lot of lamenation on her verses. These themes were born thanks to the nomadic life of Arab people.